Oil prices and its dependence on oil reserves - Polách, Jiří; Virglerová, Zuzana (Univerzita Pardubice, 2011)
Oil is a strategic raw material with many uses, mainly as a source of energy. As such energy source nowadays it cannot be replaced efficiently. More often oil is a reason for wars and disputes. It is exhaustible source of energy, with reduction in time. Lower supply and growing price are thus interconnected. Article is trying to find dependence of oil price on its reserves and predict the possible price development in the future, based on historical data about reserves and average oil prices. First, an oil production sector is analyzed, using SWOT analysis and analysis of offer and demand. On the side of offers there are countries named with biggest oil fields and than world supply as a whole. On the side of demand biggest oil users are defined and development of world needs for this raw material. Next, using Pearson correlation and Spearman ranks correlation coefficient a research was performed on dependence of two values (average oil price and oil supply during each year since 1980). Using polynomials a chart is build regarding future oil pricing, calculated from past development of quantities mentioned.
Keywords: oil; supply; price; economic; consumption